An Ascertainment of Multi-Sectorial Programs for Trade and Aid between Pakistan and South Korea; Challenges, Opportunities and Way Forward - Khan, Mohsin (Journal of Asian Business Strategy, 2015)
The rapid and unprecedented social, economic growth, advancement in science and technology and improved governance in Republic of Korea embarked a new miracle in the history of the world. With an aim to explore and materialize these tremendous development experiences’ the current study examine the existing trends, opportunities and potential sectors in Pakistan for sustainable economic development and suggested way forward to strengthen the cooperation between Pakistan and republic of Korea. The present study provide a descriptive analysis of both countries bilateral trade and ongoing cooperation and provide future strategy for utilizing certain developments which can revitalize Pakistan economy. The paper suggested that government and policy makers should consider the evolving nature of both countries and mutual interests through consultative meetings, visits and joint analysis. In sum, Pakistan and Korea can enjoy a mutually beneficial relationship as they enter a new era of friendship and Pakistan certainly will turn into another land of opportunity for Korea.